2001
DOI: 10.1038/ng704
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant regulation of insulin receptor alternative splicing is associated with insulin resistance in myotonic dystrophy

Abstract: Myotonic dystrophy type 1 (DM1) is caused by a CTG trinucleotide expansion in the 3' untranslated region of the DM protein kinase gene. People with DM1 have an unusual form of insulin resistance caused by a defect in skeletal muscle. Here we demonstrate that alternative splicing of the insulin receptor (IR) pre-mRNA is aberrantly regulated in DM1 skeletal muscle tissue, resulting in predominant expression of the lower-signaling nonmuscle isoform (IR-A). IR-A also predominates in DM1 skeletal muscle cultures, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

33
749
1
7

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 711 publications
(790 citation statements)
references
References 39 publications
33
749
1
7
Order By: Relevance
“…In addition, it has been suggested that the insulin resistance that occurs in DM1 muscles may be the consequences of alteration in the splicing of insulin receptor pre-mRNA caused by the increased expression of CUG-binding proteins. 34 We showed that the defective action of insulin on glucose uptake retained in DM1 muscle cell cultures was also completely restored in (CUG) 13 antisense-infected DM1 myoblasts. Thus, decreased levels of mutant DMPK transcripts by the antisense inhibit the abnormal upregulation of the total levels of CUG-binding protein that may counteract the aberrant regulation of the insulin receptor and restore the action of insulin on glucose uptake in DM1 myoblasts.…”
Section: Targeting Of Mutant Dmpk Transcripts D Furling Et Almentioning
confidence: 82%
“…In addition, it has been suggested that the insulin resistance that occurs in DM1 muscles may be the consequences of alteration in the splicing of insulin receptor pre-mRNA caused by the increased expression of CUG-binding proteins. 34 We showed that the defective action of insulin on glucose uptake retained in DM1 muscle cell cultures was also completely restored in (CUG) 13 antisense-infected DM1 myoblasts. Thus, decreased levels of mutant DMPK transcripts by the antisense inhibit the abnormal upregulation of the total levels of CUG-binding protein that may counteract the aberrant regulation of the insulin receptor and restore the action of insulin on glucose uptake in DM1 myoblasts.…”
Section: Targeting Of Mutant Dmpk Transcripts D Furling Et Almentioning
confidence: 82%
“…We suggest two possible explanations for a low FcRn affinity for IgG based on the current notion that patients with DM manifest a generalized defect in pre-mRNA processing [37][38][39]. Perhaps the FcRn α-chain itself is abnormally spliced in a subtle but critical fashion such that the IgG binding site is distorted while the albumin binding site is preserved.…”
Section: Pathophysiology Of Dm a Second Putatively Fcrn-related Diseasementioning
confidence: 93%
“…DM is a genetic disease manifesting what appears to be a generalized defect in pre-mRNA processing [37][38][39]. Its phenotype is different from FHH.…”
Section: Pathophysiology Of Dm a Second Putatively Fcrn-related Diseasementioning
confidence: 99%
“…Mis-regulation by MBNL1 and CUGBP1 acts synergistically in the splicing misregulation of a wide group of developmentally regulated genes (Kanadia et al, 2003). These include the IR (insulin receptor gene; Savkur et al, 2001), c-TNT (cardiac troponin T gene; Philips et al, 1998), CLCN1 (muscle chloride channel 1 gene; Mankodi et al, 2002), and those encoding dystrophin (Nakamori et al, 2007) and microtubule-associated tau (Sergeant et al, 2001). Any alterations in the CLCN1, IR and c-TNT RNA splicing can cause myotonia, insulin resistance and cardiac defects respectively .…”
Section: Nuclear Rna Retentionmentioning
confidence: 99%